CSC034: Fundamentals of Information and Communication Technology / Centre of Foundation Studies - UiTM, Centre of Foundation Studies (Universiti Teknologi MARA (UiTM), 2023)
This course exposes students to the fundamentals of computer and deals with general computer literacy. The course also explain the current computing trend in Industry Revolution 4.0 on managing Data, Cloud Computing and Interactive Multimedia Applications. This course also emphasizes the aspect of computer security and computing ethics. Students are expected to have hands-on experience on basic application tools.